PENGARUH KARAKTERISTIK INDIVIDU, KARAKTERISTIK PEKERJAAN DAN DUKUNGAN SOSIAL TERHADAP KEPUASAN KERJA KARYAWAN PUSKESMAS SE KECAMATAN AMPEAN - Sulaimiah Sulaimiah; Djoko Supyateno; Sarifudiin Serif; Zainal Abidin (Distribusi - Journal of Management and Business, 2020)
This study aims to analyze the effect of individual characteristics on job satisfaction, the effect of job characteristics on job satisfaction, the effect of social support on job satisfaction in puskesmas in Ampenan sub-district, especially ampenan health center, pejeruk puskesmas and Karang pule puskesmas, using 62 respondents as samples in the study this. This type of research is a questionnaire, causal associative research, with primary data sources and with questionnaire methods, documentation and interviews if there are respondents' answers that are unclear and need a more detailed explanation, as a crosscheck. The results obtained are all valid and reliable questionnaires, and all independent variables namely individual characteristics, job characteristics, social support have a positive and significant effect on employee job satisfaction, because the r count obtained> r table, and social support variables are the dominant variables in the appeal variables of individual characteristics and job characteristics influence on job satisfaction. Suggestions that can be proposed on how to increase job satisfaction by increasing job characteristics especially, the need for better explanations of the demands and targets of work that must be done by employees so that they are better prepared to work, provide learning or training to complement work experience that is still lacking or still new, and once in a while approach the family, the community to increase social support at work, to increase job satisfaction.